Keterkaitan Pemilihan Keberagaman dengan Status Gizi Anak - Ulfia Fitriani Nafista; Nani Nurhaeni; Imami Nur Rachmawati (FORIKES, 2022)
The nutritional status of children is critical, especially in the early stages of child growth. Inadequate child nutrition will cause stunting, wasting, and even obesity problems. One of the factors related to the nutritional status of children is the diversity of children's food, especially during the complementary feeding phase. This article was a systematic review that discusses the relationship between the diversity of complementary foods in children and nutritional status. Search sources were Science Direct, Scopus, Wiley Online Library, Sage Pub Journal, and Clinical Key published from 2016-2021. The results showed that various complementary foods positively impact and can reduce the risk of impaired child development. Therefore, parents need to provide a variety of foods according to the existing recommendations to maintain the nutritional status of children.Keywords: complementary feeding; dietary diversity; nutritional status ABSTRAK Status gizi anak sangat penting terutama pada masa awal pertumbuhan anak. Ketidakadekuatan gizi anak akan menimbulkan masalah seperti stunting, wasting bahkan obesitas. Salah satu faktor yang berhubungan dengan status gizi anak adalah keberagaman makanan anak terutama pada fase pemberian MPASI. Artikel ini merupakan systematic review yang membahas hubungan keberagaman MPASI anak dan status gizi. Sumber pencarian adalah Science Direct, Scopus, Wiley Online Library, Sage Pub Journal, dan Clinical key yang diterbitkan dari 2016-2021. Hasil menunjukkan bawah pemberian makanan MPASI yang beragam memiliki dampak positif dan mampu mengurangi risiko gangguan tumbuh kembang anak. Oleh karena itu penting bagi orang tua untuk memberikan makanan yang beragam sesuai anjuran yang ada untuk menjaga status gizi anak.Kata Kunci: keberagaman makanan; MPASI; status gizi